Productividad y felicidad: las personas más productivas son más felices? - Francisco Javier Aliaga; Marcelo Gantier Mita; Alejandro Herrera Jiménez (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2015)
– The Economics of Happiness is an area of the economy that emerged as an alternative for measuring the quality of life of people from the perspective of subjective well-being. Most of happiness studies study the determinants of happiness and relationships with economic, social and psychological variables. In this context exist evidence of a positive correlation between happiness and productivity of workers. However, some authors argue that the causality between the two variables can go in both ways. The following paper analyzes the shape in which a increment of productivity self-declared of people that live in the city of La Paz, reflects changes in their level of subjective well-being using data panel and cross-sectional analysis. To this end three variables are analyzed, the first consists in levels of productivity self-reported by individuals over time, the last two are proxy measures of productivity. Among the most important findings is found that people who declare themselves more productive are happier, however, when productivity is measured with more objective proxy variables it shows that productivity could be affecting other dimensions such as family or social relationships which reduces happiness.
Keywords: D03; J24; 330; Economics of Happiness; Determinants of Happiness; Productivity